2022
DOI: 10.1002/jssc.202100700
|View full text |Cite
|
Sign up to set email alerts
|

Dried plasma spot–based liquid chromatography–tandem mass spectrometry for the quantification of methotrexate in human plasma and its application in therapeutic drug monitoring

Abstract: Methotrexate, a folic acid antitumor drug, is widely used to treat childhood acute lymphoblastic leukemia. Therapeutic drug monitoring is crucial for adjusting the dosage of methotrexate according to its plasma concentration and reducing adverse effects. Micro‐sampling strategies, like dried plasma spot, is an attractive but underutilized method that has the desired features of easy collection, storage, and transport, and overcomes known hematocrit issues in dried blood spot analysis. This study describes a dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…With ultrahigh sensitivity, specificity, and analysis speed, mass spectrometry (MS) has been becoming an exciting analytical technology for increasingly more clinical applications, including identification of microbes, newborn screening (NBS), and quantification of therapeutic drugs. , Nowadays, nearly all clinical MS analyses are performed using laboratory-scale mass spectrometers typically coupled with a gas chromatograph (GC) or liquid chromatograph (LC), which is always labor-intensive and time-consuming. As a result, these MS techniques are limited to only in-lab applications and cannot meet the increasing demands of in situ clinical analysis, especially point-of-care testing (POCT).…”
Section: Introductionmentioning
confidence: 99%
“…With ultrahigh sensitivity, specificity, and analysis speed, mass spectrometry (MS) has been becoming an exciting analytical technology for increasingly more clinical applications, including identification of microbes, newborn screening (NBS), and quantification of therapeutic drugs. , Nowadays, nearly all clinical MS analyses are performed using laboratory-scale mass spectrometers typically coupled with a gas chromatograph (GC) or liquid chromatograph (LC), which is always labor-intensive and time-consuming. As a result, these MS techniques are limited to only in-lab applications and cannot meet the increasing demands of in situ clinical analysis, especially point-of-care testing (POCT).…”
Section: Introductionmentioning
confidence: 99%
“…28 In another study in patients with lymphoblastic leukaemia, DPS and wet plasma concentrations of methotrexate were found to have no statistically significant difference. 117 However, DPS from Telimmune cards have been shown…”
Section: Therapeutic Drug Monitoringmentioning
confidence: 99%
“…Evaluation of methotrexate polyglutamates in different matrices including plasma, RBCs, peripheral blood mononuclear cells and venous whole blood revealed that VAMS can be used for accurate TDM analysis only if sampling is done immediately before the next dose of methotrexate to ensure that concentrations are not overestimated 28 . In another study in patients with lymphoblastic leukaemia, DPS and wet plasma concentrations of methotrexate were found to have no statistically significant difference 117 . However, DPS from Telimmune cards have been shown to produce inconsistent filtration across different cards, in the study by Tang et al., for the quantification of giredestrant, stipulating the need for further optimization to ensure good accuracy and precision 118 .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several disadvantages should be recognized, such as calibration to the particular drug, the imprecise results at low plasma levels, and none of the methods being specific enough for quantifying all DOACs in a single run [10]. LC-MS/MS presents a golden standard and powerful technique for multiple drug analysis [11][12][13], including DOACs monitoring in preclinical drug development [14,15]. Due to the high degree of specificity, sensitivity, and selectivity over the coagulation-based assays, the use of LC-MS/MS in clinical laboratories has significantly increased in past years for DOAC monitoring [16].…”
Section: Introductionmentioning
confidence: 99%